PERSEPSI PEDAGANG SAYURAN DAN BUAH TERHADAP PASAR INDUK SURABAYA SIDOTOPO - Moh Heru Alfin Maulana; Teguh Soedarto; Nisa Hafi Idhoh Fitriana (Agriculture Faculty of Flores University, 2026)
The Surabaya Sidotopo Central Market plays a crucial role as a distribution hub and a driver of the local economy in East Java, yet it faces serious challenges such as a high proportion of vacant stalls (46.67%) and competitive pressure from modern markets. This study aims to analyze the perspectives of vegetable and fruit vendors regarding market management to increase their income, using a descriptive quantitative approach via a Likert-scale questionnaire administered to 67 vendors (34 vegetable vendors, 33 fruit vendors). The results indicate that vendors’ perceptions are generally positive, with a total score of 54.15 (the “Good” category), where cleanliness and facilities received the highest score (11.16), followed by social relationships (11.07), regulations (10.83), business sustainability (10.59), and innovation (10.50), while the main challenges include regulatory fairness, competition, and low adoption of digitalization. Theoretically, this study contributes by providing a multidimensional analytical framework that can be adapted to similar markets in other cities; practically, these findings provide data-driven guidance for managers to prioritize interventions ranging from infrastructure improvements, regulatory outreach, leadership training, and community empowerment to the adoption of digital technologies in order to strengthen the competitiveness of traditional markets and support the well-being of vendors as well as local economic stability.